Burkholderia pseudomallei Differentially Regulates Host Innate Immune Response Genes for Intracellular Survival in Lung Epithelial Cells. - Kumutha Malar Vellasamy; Vanitha Mariappan; Esaki M Shankar; Jamuna Vadivelu (Public Library of Science (PLoS), 2016)
BACKGROUND:Burkholderia pseudomallei, the causative agent of melioidosis poses a serious threat to humankind. B. pseudomallei secretes numerous virulence proteins that alter host cell functions to escape from intracellular immune sensors. However, the events underlying disease pathogenesis are poorly understood. METHODS:We determined the ability of B. pseudomallei to invade and survive intracellularly in A549 human lung epithelial cells, and also investigated the early transcriptional responses using an Illumina HumanHT-12 v4 microarray platform, after three hours of exposure to live B. pseudomallei (BCMS) and its secreted proteins (CCMS). RESULTS:We found that the ability of B. pseudomallei to invade and survive intracellularly correlated with increase of multiplicity of infection and duration of contact. Activation of host carbohydrate metabolism and apoptosis as well as suppression of amino acid metabolism and innate immune responses both by live bacteria and its secreted proteins were evident. These early events might be linked to initial activation of host genes directed towards bacterial dissemination from lungs to target organs (via proposed in vivo mechanisms) or to escape potential sensing by macrophages. CONCLUSION:Understanding the early responses of A549 cells toward B. pseudomallei infection provide preliminary insights into the likely pathogenesis mechanisms underlying melioidosis, and could contribute to development of novel intervention strategies to combat B. pseudomallei infections.